Antigenic Differences in Newcastle Disease Viruses Isolated in Iran - Hemmatzadeh, F.; Nayeri, B.; Tofighi, E.R. (International Journal of Poultry Science, 2006)
The samples included 30 velogenic strains of NDV, isolated from diseased chicks during 3 years period, and 2 vaccinal strains were cultured on chicken embryo and then concentrated and purified by ultra centrifugation. All samples were electrophoresed on 12.5% SDS-PAGE gels for staining and Western blotting using anti-NDV antibody. Six different antigens with molecular weigh 79, 75, 64, 40, 36 and 27 were detected in viral proteins and in some of the isolates a 48-49 kDa antigen were observed instead of a 64 kDa protein that had similarities to fusion protein in ND viruses. Western blot analysis of the antigenic patterns did not produce concise, discrete groupings, but did emphasize some relationships between virus properties and antigenicity.